Catching a glimpse: the visualization of Mycobacterium tuberculosis from TB patient bioaerosols - Dinkele, Ryan (Department of Pathology, 2023)
Transmission between hosts is crucial for the success and survival of the obligate human pathogen and aetiological agent of tuberculosis (TB), Mycobacterium tuberculosis (Mtb). Despite this, little is known about how and when Mtb is aerosolized nor the key metabolic and morphological determinants driving successful transmission. To address these knowledge gaps, my doctoral research sought to develop a microscopic method for the detection of aerosolized Mtb following liquidcapture within the respiratory aerosol sampling chamber (RASC). This was achieved through the combination of the mycobacterial cell wall probe, 4-N,Ndimethylamino-1,8-naphthalimide-trehalose (DMN-tre), with the arraying of bioaerosol samples on bespoke nanowell devices amenable to fluorescence microscopy. With this method, a median of 14 live Mtb bacilli (range 0-36) were detected in 90% of confirmed TB patients following 60 minutes of bioaerosol sampling. Three distinct DMN-tre staining patterns were identified among aerosolized Mtb, strongly suggestive of metabolic heterogeneity. Moreover, a low proportion of patients produced Mtb in small clumps. These observations highlight the advantages of using microscopy over conventional culture- or molecular-based techniques for probing the metabolic and morphological characteristics of aerosolized Mtb. Applying this method in a second study, we sought to understand how and when Mtb is aerosolized. To this end, we aimed to compare the aerosolization of Mtb and total particulate matter from patients with TB during three respiratory manoeuvres: tidal breathing (TiBr), forced vital capacity (FVC), and cough. Although total particle counts were 4.8-fold greater in cough samples than either TiBr or FVC, all three manoeuvres returned similar rates of positivity for Mtb. No correlation was observed between total particle production and Mtb count. Instead, for total Mtb counts, the variability between individuals was greater than the variability between sampling manoeuvres. Finally, when modelled using 24-hour breath and cough frequencies, our data indicate that TiBr might contribute more than 90% of the daily aerosolized Mtb among symptomatic TB patients. Assuming the number of viable Mtb organisms detected provides a proxy measure of patient infectiousness, this method suggests that TiBr is a significant contributor to TB transmission. In developing a novel platform for the detection of aerosolized Mtb, this work has suggested the need to re-examine old assumptions about Mtb transmission.